Severe outcomes of COVID-19 among adults with increased risk conditions: A population-based observational study. - Scott Dryden-Peterson; Andy Kim; Ellen C Caniglia; Mary-Ruth Joyce; David Rubins; Arthur Y Kim; John Fangman; Lindsey R Baden; Ann E Woolley (PLoS ONE)
Background The individual risk of severe outcomes following COVID-19 is poorly understood in populations with prior immunity. The lack of contemporary estimates limits support of timely diagnosis and antiviral treatment for individuals most likely to benefit. Objective To determine the risk of severe outcomes following COVID-19 within strata of comorbidities, including patients without documented infection. Design Population-based cohort study utilizing electronic medical records and g methods to account for selection bias in the documentation of COVID-19 illnesses. Setting A large health system in northeastern United States. Patients Adults with increased risk conditions (90% vaccinated) and COVID-19 from June to December 2022. Measurements Incidence of composite of inpatient admission within 14 days and death within 28 days of COVID-19 diagnosis. Results An estimated 265,248 patients with at least one increased risk condition developed COVID-19, including 76,996 documented cases. Severe outcomes occurred in 3344 (1.3%) patients following COVID-19- 3147 (1.2%) hospitalizations and 376 (0.14%) deaths. In the absence of treatment, individuals with few increased risk conditions (MASS of 3 or less) accounted for 57% of infections and 0.7% developed severe outcomes. In contrast, 2.3% of patients with multiple increased risk conditions (MASS 4 or greater) or severe immunocompromise experienced severe outcomes, including 81% of deaths. The observed risk reduction with antiviral treatment was -0.1% (-0.2 to 0.02%), -0.6% (-0.9 to -0.4%), -1.3% (-2 to -1%), and -1.9% (-3 to -1%) for patients with MASS 3 or less, MASS 4 and 5, MASS 6 or greater, and severe immunocompromise, respectively. Limitations Estimated number COVID-19 cases cannot be directly verified. Conclusions Individuals with multiple medical conditions remain at substantial risk for severe outcomes of COVID-19 and benefit from treatment.